2022
DOI: 10.1590/fst.34222
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metals in some commercially fishery products marketed in Saudi Arabia

Abstract: Seven major commercially important marine fisheries species, Fenneropenaeus indicus, Chaceon quinquedens, Lethrinus nebulosus, Scomberomorus commerson, Plectropomus pessuliferus, Pampus argenteus, and Epinephelus summana were seasonally sampled from Jeddah main local fisheries market, Saudi Arabia. The heavy metals, namely arsenic (As), cadmium (Cd), chromium (Cr), cobalt (Co), copper (Cu), iron (Fe), lead (Pb), nickel (Ni), and zinc (Zn) were assessed. Except for arsenic, the results indicated that the levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Heavy metals, including Cr, Al, Cd, and Pb, which were selected for study in this paper, interact with the human body through many proteins, genes, and DNA by losing one or many electrons and manufactured metals cations, which have many affinity sites to various macromolecules, and many tissues and body organs are also affected [ 6 , 17 ]. The current results for groups 1 and 2 ( Table 2 and Table 3 ) may also be due to the daily use of other cosmetics, food, or drinks, and previous research has indicated various kinds of food contamination and toxicity, including those that are manufactured or fresh [ 14 , 15 , 23 , 25 , 26 , 32 , 33 , 34 , 35 , 36 , 37 ]. Hence, the human body’s direct exposure to heavy metals from food, beverages, cosmetics, soil, air, tobacco, dust, and skin can affect internal biological systems depending upon the dose, leading to acute early effective and chronic accumulation, consequently, leading to various macromolecule infection and health issues, including deadly neurological, brain, liver, kidney, bone, skin, and other fetal diseases [ 1 , 38 ].…”
Section: Discussionmentioning
confidence: 84%
“…Heavy metals, including Cr, Al, Cd, and Pb, which were selected for study in this paper, interact with the human body through many proteins, genes, and DNA by losing one or many electrons and manufactured metals cations, which have many affinity sites to various macromolecules, and many tissues and body organs are also affected [ 6 , 17 ]. The current results for groups 1 and 2 ( Table 2 and Table 3 ) may also be due to the daily use of other cosmetics, food, or drinks, and previous research has indicated various kinds of food contamination and toxicity, including those that are manufactured or fresh [ 14 , 15 , 23 , 25 , 26 , 32 , 33 , 34 , 35 , 36 , 37 ]. Hence, the human body’s direct exposure to heavy metals from food, beverages, cosmetics, soil, air, tobacco, dust, and skin can affect internal biological systems depending upon the dose, leading to acute early effective and chronic accumulation, consequently, leading to various macromolecule infection and health issues, including deadly neurological, brain, liver, kidney, bone, skin, and other fetal diseases [ 1 , 38 ].…”
Section: Discussionmentioning
confidence: 84%
“…Moreover, a study contacted in Jeddah, Saudi Arabia, which examined five fish samples [50], showed that the values of most identified metals were within permissible limits, as shown in Table 2. An exception is the high As values found in Lethrinus nebulosus (0.23-0.26 mg/kg), Plectropomus pessuliferus (0.21-0.26 mg/kg), and Epinephelus summana (0.21-0.23 mg/kg).…”
Section: Case Studies In Asiamentioning
confidence: 97%
“…As-0.53-0.75 (mg/kg) Pb-ND Co-2.18-2.35 (mg/kg) Ni-ND Cu-ND Zn-1.01-2.62 (mg/kg) Fe-4.60-5.75 (mg/kg) Cd-0.21-0.25 (mg/kg) Cr-1.80-2.50 (mg/kg) (Aljabryn, 2022) [5] Fish (Chaceon quinqueden)…”
Section: Shrimp (Fenneropenaeus Indicus)mentioning
confidence: 99%